Wildlife substitution equivalents based on metabolisable energy for calculating stocking densities on Southern African wildlife ranches - CA Shepstone; N van Rooyen; MW van Rooyen; J du P Bothma; REJ Burroughs (South African Journal of Animal Science, 2025)
This study aims to bridge the gap between the large stock unit method and the grazer and browser unit methods for estimating the stocking densities of wild herbivore ungulates on wildlife ranches and reserves using both extensive and intensive production methods. Animal substitution equivalents based on metabolisable energy are calculated to estimate stocking densities; however an annual up-to-date vegetation evaluation is required to estimate the carrying capacity of the habitat to support wild herbivore ungulates without it being degraded over time. This study provides an applied approach to how refined large stock, wild herbivore, grazer, and browser unit equivalents can be used effectively. The two production methods described differ in their intensity of animal management. In the extensive wild herbivore ungulate production method, the mean animal mass is used to calculate the large stock, wild herbivore, grazer, and browser substitution equivalent units, while in the intensive wild herbivore ungulate production method, the mean mass per physiological state, with varying percentages of suckling offspring, is used to do so. These methods are extrapolated from mean linear transformations of the different physiological states and sexes of the different types of herbivores. The extensive wild herbivore ungulate production method is preferred when evaluating wildlife ranches focused on hunting and tourism, as wildlife census data do not incorporate the numbers of males, females, and offspring, whereas the intensive wild herbivore ungulate production method is preferred for intensive breeding systems in which the numbers of males, females, and offspring are known.